The Papers of Thomas A. Edison Menlo Park: The Early Years, April 1876-December 1877 - Edison, Thomas A. (Johns Hopkins University Press, 1994)
The third volume of this widely acclaimed series reveals the breath-taking intensity, intellectual acumen, and vast self-confidence of twenty-nine-year-old Thomas Edison. In the depths of the 1870s depression, he moved his independent research and development laboratory from industrial Newark to pastoral Menlo Park, some fifteen miles to the south on the main line of the railroad from New York to Philadelphia. There, equipped with resources for experimental development that were extraordinary for their time, Edison and a few close associates began twenty months of research that expanded their well-established accomplishments in telegraphy into pioneering work on the telephone. Edison's ideas and techniques from telegraph message recording and the telephone next led to his invention of the phonograph, the first patent for which was filed in December 1877. This invention ultimately gave Edison a world-wide reputation-and the nickname "the wizard of Menlo Park."